Information System Criticism and Suggestions for Optimizing Services at the Padang Tualang Subdistrict Office, Web-Based Using the CodeIgniter Framework - Tama, Adistya; Amin, Muhammad; Ramadhan, Zuhri (Bahasa Indonesia, 2024)
Study This aim For develop A System Information Critics and Designed web- based Suggestions For increase quality services at the Padang Tualang District Head Office . System This built uses the CodeIgniter framework , which is known with his abilities in build dynamic web applications And structured . With exists system this , society can with easy convey critics and their suggestions in a way direct and real-time, so party subdistrict can respond And follow up input the with more fast And effective . Feature main from system This covers form submission critics and suggestions, administration dashboard For management input , as well report And data analysis for help in taking decision . Testing system show that use this web technology can in a way significant increase participation public in the process of upgrading service public And provide constructive feedback . Implementation system This expected can become a model for other sub-districts in increase quality service public through utilization technology information .